(untitled) (Argos, 2025)
To Parmenides, philosophy is the way conducting to the understanding of the basic and fundamental meaning of the fact of being. Truth (aletheia) consists in grasping the sense of "it is". To devaluate or to ignore the absolute meaning of the fact of being produce "opinions" (doxai). There is not, for Parmenides, a midway between "truth" and "opinions". Up to the end of XIXth century, all interpretations of Parmenides’ philosophy respected this principle. A wrong conjecture proposed to complete a truncated verse (the verse 6.3), consecrated for H. Diels in 1882, gave erroneously the idea that, besides the way of truth, it would be possible to admit two false ways, and, in this case, the ways of inquiry would be "three". A simple reject of the conjecture of Diels shows that this virtual "third" way does not exist.